Teacher Professional Development in the Integration of Digital Technologies for Teaching and Learning at Selected South African Schools - Olika , Moila; Moses , Makgato; Sibongile , Simelane-Mnisi (Online Journal for TVET Practitioners, 2019)
The use of digital technologies for pedagogical purposes is a major factor for the enhancement of teaching and learning practices in the digitalized world. The purpose of this study was to investigate teacher professional development (TPD) in the integration of digital technologies for teaching and learning. Qualitative approach was used in this study. Participants were 91 teachers from public secondary schools in Tshwane South District 4 in Gauteng, South Africa. Data was collected by means of individual interviews. Data were analyzed manually using patterns, categories, codes and themes. Findings revealed that there was evidence of inadequate digital technology teacher professional development programs (DTTPDPs) received by teachers. There was lack of time; lack of support; and lack of effective planning for DTTPDPs particularly on the integration of digital technology in the curriculum. Results also shows that 75 (89%) of the teachers indicated that they would like to attend more of pedagogical DTTPDP related to the subjects that they teach. It is evident that despite having had several initiatives relating to digital technology teacher professional development (DTTPD in the district, there is still need for more effective such development for most teachers. Based on the findings, the researchers recommend that the Department of Basic Education (DBE) develop and implement effective DTTPDP strategies to urgently address the current lack of meaningful and effective DTTPDs.